2014
DOI: 10.1002/cbdv.201400070
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxic Potential of Onopordum acanthium L. (Asteraceae)

Abstract: Onopordum acanthium L. (Asteraceae) is a plant native to southern Europe and southwestern Asia, but it is invasive in disturbed areas and agricultural fields around the world, causing many agronomic problems by interfering with crops or preventing animals from grazing on pastures. Allelopathy could be one of the reasons that this plant has spread over different continents. The aim of the present study was to bioprospect O. acanthium leaf extracts through the isolation and purification of allelopathic secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 54 publications
(51 reference statements)
0
6
0
1
Order By: Relevance
“…In addition, the C. cardunculus crude methanolic extract had the best herbicidal activity in post-emergence under greenhouse conditions. C. cardunculus leaves are known to be a good source of polyphenols (Omezzine et al, 2011;Falleh et al, 2008) The herbicidal activity of phenolic extracts in pre-emergence is widely documented (Javaid et al, 2010;Araniti et al, 2015;Watanabe et al, 2014;Nekonam et al, 2014;Bessada et al, 2015;Uddin et al, 2014;Ma et al, 2018;Schleiden et al, 2019), but to our knowledge no study had yet focused on their effect in post-emergence by direct spraying on weed leaves. C. cardunculus, which is well known for its coagulant properties (Prados & Pino, 2007) and phytotoxic effect in pre-emergence (Rial et al, 2014;Rial et al, 2016;Scavo et al, 2019), is unveiled for the first time for its herbicidal effect in post-emergence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the C. cardunculus crude methanolic extract had the best herbicidal activity in post-emergence under greenhouse conditions. C. cardunculus leaves are known to be a good source of polyphenols (Omezzine et al, 2011;Falleh et al, 2008) The herbicidal activity of phenolic extracts in pre-emergence is widely documented (Javaid et al, 2010;Araniti et al, 2015;Watanabe et al, 2014;Nekonam et al, 2014;Bessada et al, 2015;Uddin et al, 2014;Ma et al, 2018;Schleiden et al, 2019), but to our knowledge no study had yet focused on their effect in post-emergence by direct spraying on weed leaves. C. cardunculus, which is well known for its coagulant properties (Prados & Pino, 2007) and phytotoxic effect in pre-emergence (Rial et al, 2014;Rial et al, 2016;Scavo et al, 2019), is unveiled for the first time for its herbicidal effect in post-emergence.…”
Section: Discussionmentioning
confidence: 99%
“…The greatest herbicidal activity was obtained using extracts from two Asteraceae plants (A. herbaalba and C. cardunculus), which inhibited seed germination and seedling growth of three weeds. The Asteraceae family has been found to harbour the most prominent biocidal substances for agriculture and to be a good source for isolating and purifying allelopathic secondary metabolites (Bessada et al, 2015;Watanabe et al, 2014). In addition, the C. cardunculus crude methanolic extract had the best herbicidal activity in post-emergence under greenhouse conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Further experiment revealed that β-eudesmol (10.10%), which was a dominant compound in flower oil but not detected in leaf and stem oils, was most likely responsible for the potent phytotoxic activity of flower oil by comparing the strength of β-eudesmol and flower oil. β-eudesmol was found to possess antiangiogenic, antimutagenic, anticancer, antioxidant activity and so on, however there is no report on its phytotoxicity 21 , 31 36 .…”
Section: Discussionmentioning
confidence: 99%
“…4’-methyl ether of scutellarein (6-hydroxy apigenin) was found in leaves in the amount of 9.5 mg per 215 g of dry leaves [26]. Other methoxy derivatives (nepetin, chrysoeriol, hispidulin, pectolinarigenin) were detected in the aerial part in the amount of 8.0 mg/4.4 kg dry raw material (nepetin), 3.5 mg/4.4 kg dry raw material (hispidulin), as well as in leaves and 1.6 mg/215 g dry weight (pectolinarigenin) and flowers (chrysoeriol) [23,24,25,26].…”
Section: Chemical Compositionmentioning
confidence: 99%